Prawno-kryminalistyczna problematyka przesłuchania małoletniego w procedurach prawnych - Zieniewicz, Iwona (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
The children witness hearing belongs to special trial activities and requires a special approach of judges, prosecutors, policemen who are responsible for its conduct. The most extensive regulations are those concerning witness hearing in a criminal proceding. In civil and administrative procedure the regulations are evaluated as insufficient. The person questioning the children has to have psychological and forensic science knowledge. Those fields of science formulate the tactical rules of child hearing. Their first aim is the protection of children from negative results of participation in law trials and the second aim is to receive trusted information concerning circumstances of law case. This publication is presenting the tactical rules which can be used in law proceedings.
Keywords: świadek - dziecko; przesłuchanie dziecka; psychologia; kryminalistyka; ochrona dziecka w postępowaniu sądowym